Negotiating Islamic Moderation: The Interplay of Sharia and Local Culture in Gorontalo, Minangkabau, and Banten - Suleman, Zulfitri Zulkarnain; Tungkagi, Donald Qomaidiasyah; Suleman, Zulkarnain; Kau, Sofyan A.P.; Salleh, Mohd Afandi (IAIN Manado, 2025)
Muslim scholars and local communities have actively negotiated the Islamization process in Indonesia through complex engagements with Islamic law (sharia) and local cultural traditions. This study examines how such interactions have shaped distinct constructions of Islamic moderation in three culturally significant regions: Gorontalo, Minangkabau, and Banten. Employing a qualitative, field-based approach, the research utilizes in-depth interviews, participant observation, and document analysis to explore the integration of sharia and adat (customary law). The findings reveal three typological models of Islamic moderation: (1) an integrative model in Gorontalo, where royal diplomacy and political marriage internalized Islamic law within the framework of customary governance; (2) a negotiation model in Minangkabau, emerging from post-conflict reconciliation between ulama and customary leaders, institutionalized through the philosophy of Adat basandi syarak, syarak basandi Kitabullah; and (3) a hegemonic model in Banten, characterized by the dominance of Islamic law over local traditions, embedded within the centralized religious authority and state power. These findings suggest that Islamic moderation in Indonesia is not a singular concept but the product of historically and contextually embedded legal-cultural dynamics. The study concludes that Islamic moderation is a localized negotiation among legal norms, cultural practices, and power structures. Its academic contribution advances the understanding of legal pluralism in Muslim societies while offering policy-relevant insights for promoting religious tolerance and cultural inclusivity in Indonesia.